Segmental deficiency of cervical tracheal rings masquerading as complete tracheal rings: A case report and literature review. (October 2017) - Wineland, Andre M.; Thomsen, James R.; Landry, April; Benscoter, Dan; Rutter, Michael
Abstract: Congenital deficiency of distal tracheal rings is a rare anomaly and has been previously reported in the literature. Here we report the first case deficient tracheal rings confined to the cervical trachea. Patient was transferred to our institution for management of what was initial thought to be complete tracheal rings. The patient was successfully managed with a tracheal resection and short segment cervical slide tracheoplasty. Presentation, surgical approach, histological findings, and literature review are described.